Pengaruh Iklim Organisasi terhadap Kepuasan Kerja yang Dimediasi Komitmen Organisasional - Arif Subagiyo; Rahayu Puji Suci; Yekti Intyas Rahayu (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this study was to determine the effect of organizational climate on job satisfaction with organizational commitment as a mediating variable (study on UD Sehati Kecap Koki Dolar employees in Tulungagung). The population in this study were all employees and employees who worked at UD Sehati Kecap Koki Dolar in Tulungagung. The sampling method in this study uses the census technique or saturated sample because the population is not too large, namely 60 respondents. Data is processed through Smart Partial Least Square (PLS) software. The results showed that a better organizational climate can increase job satisfaction and organizational commitment. Meanwhile, stronger organizational commitment is also proven to affect job satisfaction. Organizational commitment acts as a mediator of the effect of organizational climate on employee job satisfaction at UD Sehati Kecap Koki Dolar in Tulungagung.